The effect of drainage ditches on vegetation diversity and CO2 fluxes in a Molinia caerulea‐dominated peatland. Issue 3 (21st May 2015) - Gatis, Naomi; Luscombe, David J.; Grand‐Clement, Emilie; Hartley, Iain P.; Anderson, Karen; Smith, David; Brazier, Richard E.
Abstract: Peatlands are recognized as important carbon stores; despite this, many have been drained for agricultural improvement. Drainage has been shown to lower water tables and alter vegetation composition, modifying primary productivity and decomposition, potentially initiating peat loss. To quantify CO2 fluxes across whole landscapes, it is vital to understand how vegetation composition and CO2 fluxes vary spatially in response to the pattern of drainage features. However, Molinia caerulea ‐dominated peatlands are poorly understood despite their widespread extent. Photosynthesis (PG600 ) and ecosystem respiration (REco ) were modelled (12 °C, 600 µmol photons m −2 s −1, greenness excess index of 60) using empirically derived parameters based on closed‐chamber measurements collected over a growing season. Partitioned below‐ground fluxes were also collected. Plots were arranged ⅛, ¼ and ½ the distance between adjacent ditches in two catchments located in Exmoor National Park, southwest England. Water table depths were deepest closest to the ditch and non‐significantly ( p = 0·197) shallower further away. Non‐ Molinia species coverage and the Simpson diversity index significantly decreased with water table depth ( p < 0·024) and increased non‐significantly ( p < 0·083) away from the ditch. No CO2 fluxes showed significant spatial distribution in response to drainage ditches, arguably due to insignificant spatial distribution of water tables and vegetation composition. Whilst REco showed no significant spatial variation, PG600 varied significantly between sites ( p = 0·012), thereby controlling the spatial distribution of net ecosystem exchange between sites. As PG600 significantly co‐varied with water table depths ( p = 0·034), determining the spatial distribution of water table depths may enable CO2 fluxes to be estimated across M. caerulea ‐dominated landscapes. © 2015 The Authors. Ecohydrology published by John Wiley & Sons, Ltd.